PENGARUH LKPD FISIKA BERORIENTASI STRATEGI PEMECAHAN MASALAH TERHADAP PENCAPAIAN KOMPETENSI PESERTA DIDIK KELAS X SMAN 1 LUBUK ALUNG - Nurhayati Fitri; Amali Putra; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2017)
One of the factors that cause low learning outcomes of learners is the low ability of learners in solving physics problems. This problem solving ability can be improved through learning using LKPD of physics by orient problem-solving strategy toward the achievement of the competence of students of Class X SMAN 1 Lubuk Alung. The purpose of this study is to investigate the effect of LKPD physics-oriented problem-solving strategies to the achievement of competence learners.The type of research conducted is quasi experiment with randomized control group design postest only design. The study population included all MIA class X students enrolled in the even semester of the academic year 2016/2017. Sampling was done by cluster random sampling technique. Research data is the value of competence knowledge, attitude and skills of learners. The research instrument is the final test to measure the knowledge competence, the observation sheet to measure the attitude competency, the performance appraisal sheet to measure the competency of the skill. The research data were analyzed by two-equation equality test. Two average equality tests were performed for the learning result value of each competency of the two sample classes.Based on the data analysis, the average score for the experimental class and control class are 83,47 and 78,16, the attitude competence is 87,04 and 79,8 and the skills competence is 88,7 and 83 , 3. Data for the knowledge, attitude and skill competencies of the two sample classes are normally distributed and have homogeneous variance, so that the two equality tests are tested with t test. From the calculation results obtained t count value for knowledge competence that is 2.773 and t table = 2,00; On attitude competence obtained t arithmetic that is 7,1911 and t table = 2,00; And on skill competence t obtained is 4.189 and t table = 2,00. In the three competencies are obtained t arithmetic> t table, means t count is outside the acceptance area Ho, so Hi accepted. Thus, the conclusion of this research is there is a significant influence from the application of LKPD of physics by orient problem-solving strategy toward the achievement of the competence of students of Class X SMAN 1 Lubuk Alung accepted